Carbonic anhydrase XII is a marker of good prognosis in invasive breast carcinoma. - Watson, P; Chia, S; Wykoff, C; Han, C; Leek, R; Sly, W; Gatter, K; Ratcliffe, P; Harris, A (2003)
Hypoxia and pH influence gene expression in tumours, and it is becoming increasingly clear that the pattern of genes expressed by a tumour determines its growth and survival characteristics. Hypoxia-inducible factor-1 (HIF-1) is a key mediator of the cellular response to hypoxia and high HIF-1 expression has been identified as a poor prognostic factor in tumours. Recently, we identified the tumour-associated carbonic anhydrases (CA), CA9 and CA12 as hypoxia-inducible in tumour cell lines. Furthermore, we identified CA IX to be a poor prognostic factor in breast cancer. The aim of this study was to assess the prognostic significance of CA XII. CA XII expression was studied by immunohistochemistry in a series of 103 cases of invasive breast cancer and any association with recognised prognostic factors or relation with the outcome was examined. CA XII expression was present in 77 out of 103 (75%) cases and was associated with lower grade (P=0.001), positive estrogen receptor status (P<0.001), and negative epidermal growth factor receptor status (P<0.001). Furthermore, although CA XII expression was associated with an absence of necrosis (P<0.001), expression of CA XII in some high-grade tumours was induced in regions directly adjacent to morphological necrosis. Additionally, using univariate analysis, CA XII positive tumours were associated with a lower relapse rate (P=0.04) and a better overall survival (P=0.01). In conclusion, CA XII expression is influenced both by factors related to differentiation and hypoxia in breast cancer in vivo and CA XII expression is associated with a better prognosis in an unselected series of invasive breast carcinoma patients.